ASPECTS OF USE OF NZEB CONCEPT FOR BUILDINGS IN CENTRAL AND EASTERN EUROPE - ДЕШКО, В. І.; НАУМЧУК, О. С. (Technologies and Engineering, 2023)
Purpose. The aim of the work is to study various aspects of the implementation of the nZEB – concept of buildings in European countries and to identify the main problems and obstacles to the scaling and development of buildings with near zero energy consumption and the use of this experience for Ukraine. Methodology. Analysis of regulatory documents, scientific papers and practices on the use of the nZEB concept in European countries. Findings. A review of legal documents, scientific papers and practices on the implementation and consolidation of the definition of the concept of buildings with almost zero energy consumption in European countries as a complement of a highly energy efficient building and renewable energy sources, energy efficient materials and technologies was carried out. Options for a detailed assessment of the new construction of the nZEB residential sector were considered. The impact of possible climate change on the characteristics of nZEB during the life cycle, including heating and cooling needs, is analyzed. Examples of the implementation of the nZEB concept in the renovation of buildings for various purposes are given. The emphasis is on the possible inconsistency and harmonization of nZEB standards with the best financial solutions and the sequence of implementation of approaches to ensure near zero energy consumption by buildings for various purposes for different climatic regions of Europe, the main challenges and obstacles in increasing the share of use of such buildings are analyzed. Originality. Various aspects of the implementation of the nZEB concept are grouped and analyzed, from regulatory documents, government incentives, balance in the concept of energy efficient solutions and the share of renewable energy sources, to technical and cultural-behavioral barriers. Practical Value of the work lies in the use of the above approaches and the experience of European countries for scaling the houses of the nZEB concept in the conditions of Ukraine.